Preparation and Characterization of Schiff Base Ligand Complexes (Dimedone With Thiourea) - Sammer mizher ayash; Shihab, Omar Hamad; Hamadneh, Imad (Moh’D Khair) Rashid (South Eastern European Journal of Public Health, 2024)
In this study, eight complexes of this group were prepared by reacting the new ligand prepared from the reaction of dimedone with thiourea with metal chlorides of divalent (Mn, Co, Ni, Cu ,Zn, Cd) and trivalent (Fe, Cr) transition elements. These complexes were characterised by distinctive colours, melting points and solubility, and from the diagnostic results obtained, it was found that the ligand.(1E,5E)-5-carbamothioylimino)-3,3-dimethylcyclohexylidene) thiourea(L2) , that behave as dodecameric ligands with the metal ion, to which they bind through two amine groups. The octahedral shape of the complexes was suggested by IR, UV-visible, molar electrical conductivity, and magnetic susceptibility spectra, all of which indicated paramagnetic properties except for Zn and Cd, which have diamagnetic properties, and molar conductivity showed that all complexes are non-electrolytic except for Fe and Cr. The molecular formula of the complexes forming the group was determined by elemental analysis, where the elemental percentages matched the proposed molecular formula. The results measured the biological efficacy against pathogenic bacteria of the complexes showed varying efficacy. The results of antioxidant efficacy measurement using ethanol showed varying efficacy and were compared with gallic acid using DPPH as a free radical and gave different IC50 values. Density Functional Theory (DFT) measurement results showed that the chemical properties of the prepared complexes were consistent with the results of the practical part.